A synopsis and new species of Bolax Fischer von Waldheim, 1829 (Coleoptera: Scarabaeidae: Rutelinae: Geniatini) from Central America - Barria, Manuel D.; Clavijo-Bustos, Julián; Seidel, Matthias (Zootaxa, 2026)
The Central American species of Bolax Fischer von Waldheim, 1829 (Coleoptera: Scarabaeidae: Rutelinae: Geniatini) are presented, each with a diagnosis and photographs of adult habitus and aedeagus. Also, a new species from Panama is described and illustrated, raising the number of species of the genus in Central America to four: Bolax azurita new species, Bolax flaveola Bates, 1888, Bolax magna Bates, 1888, and Bolax variolosa Ohaus, 1917.